Mindfulness, cognitive fusion, and self-compassion in patients with schizophrenia spectrum disorders—A cross-sectional study - Böge, Kerem; Pollex, Franziska; Bergmann, Niklas; Hahne, Inge; Zierhut, Marco Matthäus; Mavituna, Selin; Thomas, Neil; Hahn, Eric (Frontiers in Psychiatry, 2022)
In the last decades, third wave approaches in cognitive-behavioral therapies (CBT) have shown effectiveness in treating several mental disorders, including schizophrenia spectrum disorders (SSD). Three crucial processes associated with clinical changes in patients include mindfulness, self-compassion (SC) and psychological flexibility (PF). The current study encompasses a cross-sectional design to examine the interplay of mindfulness, PF, SC and symptom severity in SSD. It was hypothesized that mindfulness is negatively correlated with symptom severity, PF mediates the negative relation between mindfulness and symptom severity, and SC moderates the link between mindfulness and PF. In total, 79 persons with SSD were recruited at the Department of Psychiatry and Neurosciences at the Charité – Universitätsmedizin Berlin. Correlations, as well as moderated mediation analyses, were performed using PROCESS with total symptom severity and negative symptom severity as outcome variables. Results show that the moderated mediation hypothesis was confirmed for negative symptom severity as the outcome measure, however, not for total symptom severity. In general, the relationship between mindfulness and PF was stronger for participants with higher SC scores in our data. Future studies should investigate the relation between mindfulness, SC, and PF regarding symptom severity in SSD in longitudinal designs while considering the impact on different outcomes and differences regarding assessment tools.